Global research trends and hotspots of hyperhidrosis: a bibliometric analysis (2008–2023) - Zhi, Tong; Zhao, Chengcheng; Xiang, Xin; Yao, Ming; Ni, Huadong (Frontiers in Surgery, 2025)
BackgroundRecent studies have demonstrated significant advancements in the treatment of hyperhidrosis. However, a bibliometric analysis of relevant studies in this field is notably lacking. This study aims to provide a detailed analysis of research trends and key areas of interest in hyperhidrosis over the last 16 years using bibliometric methods.MethodsWe searched the Web of Science Core Collection (WoSCC) database for hyperhidrosis-related publications from 2008 to 2023 and conducted bibliometric analysis using VOS viewer and the R package “bibliometrix.”ResultsThe main research institutions involved in this study are the University of São Paulo, Hospital Israelita Albert Einstein, Yonsei University and Fujian Medical University, with a total of 728 articles included from 52 countries. Authors from these institutions have published in top journals, with Dermatologic Surgery being the most popular journal and the Journal of the American Academy of Dermatology being the most cited. A total of 2,830 authors have contributed to this field, with prominent researchers including Nelson Wolosker, Paulo Kauffman, Pedro Puech-Leão, Jose Ribas Milanez de Campos, and Dee Anna Glaser. Nelson Wolosker stands out as the most co-cited author. The primary focus of research in this area is on the treatment of hyperhidrosis and the prevention of post-operative complications. Emerging re-search hotspots include keywords such as “botulinum toxin,” “oxybutynin,” “sympathectomy,” “iontophoresis,” and “compensatory sweating”.ConclusionThe most prevalent academic emphasis within this field remains the treatment of hyperhidrosis and the management of compensatory hyperhidrosis. Despite this academic preponderance, there is a compelling necessity to foster enhanced collaboration and exchange between disparate countries and institutions.